2015
DOI: 10.15288/jsad.2015.76.809
|View full text |Cite
|
Sign up to set email alerts
|

Functional Limitation, Pain, and Alcohol Use: Exploring Gender Differences in the Mediating Role of Depressive Symptoms

Abstract: ABSTRACT. Objective: This study considered the processes linking functional limitation and pain with depressive symptoms and two alcohol-related outcomes (past-month drinking and problematic drinking) over a 3-year period. Method: Data were drawn from a two-wave Miami-Dade County community study of people with physical disabilities (N = 559). Structural equation modeling was used to assess whether depressive symptoms mediated the associations among functional limitation, bodily pain, and the alcohol-related ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Among younger adults, ages 25 to 45, there is experimental evidence that acute alcohol (approximate BAC = 0.065) may be associated with increased pain threshold among women, and that subjective response to alcohol may be more strongly associated with ratings of pain relief following alcohol administration among women (Hill et al, ). Yet, there is also evidence that men with chronic pain may be more at risk of AUD and depression, as well as report a stronger association between pain, depression, and alcohol use, as compared to women (Barry et al, ; Brown, ; Manubay et al, ). Also, in a sample of adults with chronic pain, pain‐related anxiety was positively associated with alcohol‐related consequences and symptoms of alcohol dependence among males, but not females (Zale et al, ).…”
Section: Comorbidity Of Problematic Alcohol Use and Painmentioning
confidence: 99%
“…Among younger adults, ages 25 to 45, there is experimental evidence that acute alcohol (approximate BAC = 0.065) may be associated with increased pain threshold among women, and that subjective response to alcohol may be more strongly associated with ratings of pain relief following alcohol administration among women (Hill et al, ). Yet, there is also evidence that men with chronic pain may be more at risk of AUD and depression, as well as report a stronger association between pain, depression, and alcohol use, as compared to women (Barry et al, ; Brown, ; Manubay et al, ). Also, in a sample of adults with chronic pain, pain‐related anxiety was positively associated with alcohol‐related consequences and symptoms of alcohol dependence among males, but not females (Zale et al, ).…”
Section: Comorbidity Of Problematic Alcohol Use and Painmentioning
confidence: 99%
“…Problem drinking associates with greater pain and greater use of alcohol to manage pain symptoms (Brennan et al, 2005). Men experiencing chronic pain may be more at risk of AUD and depression, as well as report stronger associations between pain, depression, and alcohol use, compared to women with chronic pain (Barry et al, 2013;Brown, 2015;Manubay et al, 2015). Pain-related anxiety is also positively associated with alcohol-related problems in males, but not females (Zale et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Disabilities are often related to uncontrolled chronic pain, psychological distress, or social isolation, which are also potential drivers for substance use. 6,7 A previous study found that disability status was correlated with prescription drug misuse, 8 but a more current and nuanced characterization of psychoactive substance use among adults with functional limitations is needed.…”
Section: Introductionmentioning
confidence: 99%